Physiological Impact of One-Month Alcohol Abstinence on Heart Rate, Oxygen Saturation, Maximal Oxygen Uptake, Pulmonary Function, and Muscle Strength in a Young Adult Male: A Case-Based Analysis - Yu, JaeHo (Journal of Neonatal Surgery, 2025)
This case study investigated the physiological effects of a four-week period of alcohol abstinence on cardiopulmonary and muscular function in a healthy young adult male with a habitual moderate drinking pattern. The subject, a 26-year-old male who engaged in regular aerobic and resistance training, underwent baseline and post-intervention measurements of resting heart rate, peripheral oxygen saturation (SpO2), maximal oxygen uptake (VO2max), pulmonary function (FVC, FEV1), and muscular strength (grip strength and leg press 1RM). Post-intervention assessments demonstrated meaningful improvements in all parameters, indicating autonomic nervous system recovery, enhanced pulmonary function, and improved muscle recovery. The findings provide preliminary evidence supporting the physiological benefits of short-term alcohol cessation, even among physically active young adults.